KAJIAN ETNOPEDAGOGI PADA KAIN IDUP PANAK DI DESA TENGANAN PEGRINGSINGAN, KARANGASEM-BALI - I Gusti Ngurah Agung Panji Tresna; Kenia Naras Sauca; Niluh Putu Pebriyanti (Guna Widya: Jurnal Pendidikan Hindu, 2022)
The Tenganan Pegringsingan Village is one of the Traditional Villages located in Karangasem, Bali. The village has unique traditions and cultures that make it different from the other villages in Bali. Besides tradition, the tenganan village has a distinctive woven fabric that is known as Idup Panak woven . The Idup Panak woven comes from a remnant of  Gringsing that is used as the traditional cloth for nursing mothers. Idup Panak comes from the word 'Idup' that mean life and 'panak' that have the meaning of children. So this fabric has meaning to a child's life.This research uses qualitative methods by collecting data obtained from interview, observation and literature studies based on theory. Researchers use the basis for etnopedagogy theory that is the approach to culture-based education. Through etnopedagogy studies, there are three educational values were contained in the Idup Panak woven. The value of such education includes, the value of creative education, the value of moral education, and the value of social education. Through the three educational values contained in the Idup Panak woven, this woven fabric would have a value that would play an important role in the Tenganan village community